A systematic review of email-based reminder interventions to increase vaccine uptake. (13th November 2019) - Odone, A; Frascella, B; Balzarini, F; Oradini Alacreu, A; Signorelli, C
Abstract: Introduction: Reminder and recall interventions have been proven to be effective in increasing vaccination coverage. Emails are a popular mean of communication, and their use as a reminder method has many potential benefits: low costs, timely delivery and no restriction of content. Nevertheless, there is limited evidence that compares the advantages of using emails for vaccination reminders to other methods, on which extensive literature is already present. Methods: We conducted a systematic review following the PRISMA guidelines to analyze evidence from peer-reviewed studies on the application of email-based interventions to immunization programs. We included any measure of vaccine uptake or immunization coverage, in any target population and settings. Results: We included 11 studies in the final analysis, of which 9 were RCTs, 1 was a controlled trial and 1 a before and after study. Most studies were conducted in the US. Six studies had data on the uptake of influenza vaccination, three on HPV series completion, 1 on PPSV23, and 1 on vaccines recommended for adolescents. In 4 studies email reminders proved to be more effective in increasing vaccination uptake than no reminders. Five studies didn't show advantages of using email reminders when compared to traditional methods (phone call, mail, paper card) and digital reminders (SMS, automated phone calls). In 1 study a significantly higher increase in uptake was achieved when combining emails with Interactive Voice Response phone calls. Finally, 2 studies compared different email models. Conclusions: In conclusion, this review outlined that not enough evidence is available regarding the use of email reminders to increase vaccination uptake. Our findings suggest that the choice of reminder method should depend on the population, and future studies should analyze its cost-effectiveness and convenience in respect to other methods, and aim at improving the content of emails to increase their efficacy as a reminder method. Key messages: Based on our review of available studies, not enough evidence is available to prove the efficacy of email reminders to increase vaccine uptake. Additional evidence is needed to analyze cost-effectiveness of email reminders, convenience in respect to other methods, and to improve their content to increase their efficacy as a reminder method.